2021
DOI: 10.3390/v13071321
|View full text |Cite
|
Sign up to set email alerts
|

Comparison and Sensitivity Evaluation of Three Different Commercial Real-Time Quantitative PCR Kits for SARS-CoV-2 Detection

Abstract: Real-time reverse transcription polymerase chain reaction (RT-qPCR) is the most sensitive and specific assay and, therefore, is the “gold standard” diagnostic method for the diagnosis of SARS-CoV-2 infection. The aim of this study was to compare and analyze the detection performance of three different commercially available SARS-CoV-2 nucleic acid detection kits: Sansure Biotech, GeneFinderTM, and TaqPathTM on 354 randomly selected samples from hospitalized COVID-19 patients. All PCR reactions were performed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 18 publications
1
37
0
Order By: Relevance
“…The detection of viral infections, such as SARS-CoV-2 infections, by antigen tests has been recommended by the world health organisation (WHO) as a cheap and rapid alternative for the RT-qPCR test [26] . The detection of the virus spike protein has been one of the useful approaches to develop new antigen tests for SARS-CoV-2 infections [ 10 , 23 , [27] , [28] , [29] , [30] , [31] ]. Many of the current antigen tests are designed to detect the spike protein through the change of the electric or optical properties of a sensor [Table S1].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The detection of viral infections, such as SARS-CoV-2 infections, by antigen tests has been recommended by the world health organisation (WHO) as a cheap and rapid alternative for the RT-qPCR test [26] . The detection of the virus spike protein has been one of the useful approaches to develop new antigen tests for SARS-CoV-2 infections [ 10 , 23 , [27] , [28] , [29] , [30] , [31] ]. Many of the current antigen tests are designed to detect the spike protein through the change of the electric or optical properties of a sensor [Table S1].…”
Section: Resultsmentioning
confidence: 99%
“…Multiple analytical techniques have been demonstrated for the detection of SARS-CoV-2 virus in clinical specimens [ 8 , 9 ]. The gold standard for the detection of viral infections is RT-qPCR [10] . However, this method is time consuming, expensive and requires highly trained personnel to carry out the test.…”
Section: Introductionmentioning
confidence: 99%
“…Banko et al performed a comparative study with three PCR kits, namely, Sansure Biotech (Sansure Biotech Inc., China), GeneFinderTM (OSANG Healthcare Co., Seongnam, Korea), and TaqPathTM (Thermo Fisher Scientific, Waltham, MA, USA). They showed that the Sansure Biotech assay had greater diagnostic performance than the other two PCR kits [ 8 ]. Moore et al performed another comparative study with two PCR kits, namely, Sansure Biotech and BioGerm (Shanghai, China).…”
Section: Discussionmentioning
confidence: 99%
“…To battle the COVID-19 pandemic, accurate detection tests for SARS-CoV-2 are crucial. During this emergency, several companies developed diagnostic kits for detecting SARS-CoV-2 within a short time by compromising on kit sensitivity and specificity [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The gold standard for the diagnosis of SARS-CoV-2 infections is the qRT-PCR test that identifies the virus genetic material in nasopharyngeal swabs [ [6] , [7] , [8] , [9] ]. However, this method is time-consuming, expensive and requires well-trained technicians, sophisticated lab-based equipment [ [10] , [11] , [12] ].…”
Section: Introductionmentioning
confidence: 99%